Carbon isotope composition of plant photosynthetic tissues reflects a Crassulacean Acid Metabolism (CAM) continuum in the majority of CAM lineages - Messerschmid, Thibaud F.E.; Wehling, Judith; Bobon, Nadine; Kahmen, Ansgar; Klak, Cornelia; Los, Jessica A.; Nelson, Daniel B.; dos Santos, Patrícia; de Vos, Jurriaan M.; Kadereit, Gudrun (Perspectives in plant ecology, evolution and systematics, 2021)
•Mixture modelling analysis of 7204 δ13C values infers three clusters, opposing the expectation of two clusters from a bimodal distribution.•Well-sampled lineage specific δ13C surveys reveal continuous or discontinuous, unimodal or bimodal distribution patterns of δ13C values.•Any coding of CAM vs. C3 based on a δ13C threshold undervalues the diversity of CAM and is a likely source of error in studies of CAM evolution. The stable carbon isotope composition of plant tissues, commonly expressed as δ13C, holds a wealth of information about photosynthetic pathway, water relations and stress physiology. Crassulacean acid metabolism (CAM) is a derived form of photosynthesis that allows plants to fix carbon at a higher water-use efficiency compared to the ancestral C3 photosynthesis. While the central carbon-fixing enzyme of C3 plants, Rubisco, strongly discriminates against the heavy 13C isotope, CAM is characterized by a dual use of Rubisco and the much less discriminating PEP carboxylase as carbon-fixing enzymes, causing the δ13C values of CAM plant tissues to be generally less negative than those found in C3 plants. Past studies of δ13C variation in CAM plant lineages have repeatedly found a bimodal distribution with very few samples representative of the range around -20‰ that is intermediate between C3- and CAM-like values. Although δ13C values of facultative CAM plants have long been known to extend well into the range below -20‰, this value is often tentatively used as threshold for character coding to distinguish C3 from CAM species in studies of CAM evolution. Compiling 6623 δ13C values reported in the literature for CAM/C3 vascular plant lineages and presenting new data for 581 accessions mainly of the succulent Mesembryanthemoideae (Aizoaceae) and Aeonieae (Crassulaceae), we here investigate the diverse patterns of δ13C distribution in different plant families and sub-familial taxa and demonstrate that a bimodal distribution is not universally present in all lineages. Moreover, we show by means of mixture modelling that the bimodal distribution of δ13C values in the full dataset as well as in the very well-sampled Bromeliaceae is best described by a combination of three rather than two Gaussian distributions with one intermediary cluster between the more evident clusters of C3- and CAM-like values. In view of these results and the furthermore emerging unimodal distribution of δ13C values in Mesembryanthemoideae with mean close to -20‰, we conclude that the evident continuum between CAM and C3 photosynthesis cautions against the usage of a δ13C threshold in macroevolutionary studies. Finally, the observed diversity of δ13C distribution patterns between monophyletic lineages urges for lineage-specific reconstructions rather than a unifying model of CAM evolution.